Targeting zinc homeostasis to combat Aspergillus fumigatus infections - Vicentefranqueira, Rocío; Amich, Jorge; Laskaris, Paris; Ibrahim-Granet, Oumaima; Latgé, Jean P.; Toledo, Héctor; Leal, Fernando; Calera, José A. (Frontiers in Microbiology, 2015)
Aspergillus fumigatus is able to invade and grow in the lungs of immunosuppressed individuals and causes invasive pulmonary aspergillosis. The concentration of free zinc in living tissues is much lower than that required for optimal fungal growth in vitro because most of it is tightly bound to proteins. To obtain efficiently zinc from a living host A. fumigatus uses the zinc transporters ZrfA, ZrfB and ZrfC. The ZafA transcriptional regulator induces the expression of all these transporters and is essential for virulence. Thus, ZafA could be targeted therapeutically to inhibit fungal growth. The ZrfC transporter plays the major role in zinc acquisition from the host whereas ZrfA and ZrfB rather have a supplementary role to that of ZrfC. In addition, only ZrfC enables A. fumigatus to overcome the inhibitory effect of calprotectin, which is an antimicrobial Zn/Mn-chelating protein synthesized and released by neutrophils within the fungal abscesses of immunosuppressed non-leucopenic animals. Hence, fungal survival in these animals would be undermined upon blocking therapeutically the function of ZrfC. Therefore, both ZafA and ZrfC have emerged as promising targets for the discovery of new antifungals to treat Aspergillus infections.